The knowledge, attitudes, and behaviours of pregnant women regarding seafood consumption during the antenatal period: a qualitative study - Danielle Shine; Heshani Siriwardana; Michelle Minehan; Monica Yuri Takito; Rati Jani; Catherine R. Knight-Agarwal (BMC, 2024)
Abstract Background Maternal nutrition impacts fetal growth and development. The Food Standards Australia New Zealand (FSANZ) guidelines recommend pregnant women consume 2-3 servings (224-336 g) of fish/seafood per week to support intake of long chain omega 3 fatty acids, given adequate consumption supports numerous health benefits including reduced risk of preterm and early preterm birth. Evidence indicates that pregnant women purposely lower their fish/seafood intake, largely due to fears of methylmercury exposure. The aim of this study was to explore pregnant women's knowledge, attitudes, and behaviours regarding their fish/seafood consumption during the antenatal period. Methods Semi-structured interviews were conducted between October 2018 and December 2020 among a purposive sample of 12 pregnant women from the Australian Capital Territory (ACT). The interviews were recorded, transcribed verbatim, and analysed using an interpretative phenomenological approach. Themes were developed on the women's lived experience related to fish/seafood knowledge, attitudes, and consumption behaviour. Results The most prominent finding was widespread non-adherence to fish/seafood consumption guidelines. This was largely owing to a lack of proactive health promotion related to the health benefits of fish/seafood throughout pregnancy, including the health promoting roles of long chain omega 3 fatty acids for fetal growth and development. Three themes were identified: nutrition knowledge; sources of health promotion; and barriers and enablers to fish/seafood consumption. Conclusions To support adequate maternal consumption of fish/seafood throughout pregnancy, emphasis should be placed on the benefits of consuming this food group regularly. Additionally, pregnant women should receive education about the health promoting role of long chain omega 3 fatty acids. Dietitians are well placed to provide this information.